Elastic properties of hydrogels and decellularized tissue sections used in mechanobiology studies probed by atomic force microscopy. Issue 1 (18th August 2016) - Giménez, Alícia; Uriarte, Juan José; Vieyra, Joan; Navajas, Daniel; Alcaraz, Jordi
Abstract: The increasing recognition that tissue elasticity is an important regulator of cell behavior in normal and pathologic conditions such as fibrosis and cancer has driven the development of cell culture substrata with tunable elasticity. Such development has urged the need to quantify the elastic properties of these cell culture substrata particularly at the nanometer scale, since this is the relevant length scale involved in cell‐extracellular matrix (ECM) mechanical interactions. To address this need, we have exploited the versatility of atomic force microscopy to quantify the elastic properties of a variety of cell culture substrata used in mechanobiology studies, including floating collagen gels, ECM‐coated polyacrylamide gels, and decellularized tissue sections. In this review we summarize major findings in this field from our group within the context of the state‐of‐the‐art in the field, and provide a critical discussion on the applicability and complementarity of currently available cell culture assays with tunable elasticity. In addition, we briefly describe how the limitations of these assays provide opportunities for future research, which is expected to continue expanding our understanding of the mechanobiological aspects that support both normal and diseased conditions. Microsc. Res. Tech. 80:85–96, 2017 . © 2016 Wiley Periodicals, Inc.